Weight bearing training alleviates muscle atrophy and pyroptosis of middle-aged rats - Fu, Pengyu; Gong, Lijing; Yang, Luyao; Tang, Shuning; Ma, Fangyuan (Frontiers in Endocrinology, 2023)
Background Age-related muscle atrophy and adipose accumulation begin to occur in young and middle-aged individuals, and exercise at an early age improves body composition. Pyroptosis may play an essential role in age-related low-grade inflammation. This study aimed to explore the alleviation of muscle atrophy by weight-bearing training with increasing age via inhibition of pyroptosis. Methods Ninety 8-month-old male SD rats were randomly divided into three groups: (1) normal baseline group (N group, n = 10), sacrificed after adaptive feeding; control group (C group, n = 40); and weight-bearing running group (R group, n = 40). Blood samples, adipose tissue (AT), and extensor digitorum longus (EDL) were collected after 8, 16, 24, and 32-weeks intervention. Results The body weight, muscle mass, fat mass, plasma lipid, AT wet weight, adipocyte cross-sectional area (CSA), and apoptosis rates of AT and EDL were increased, while the muscle mass, wet weight, and fiber CSA of EDL were decreased by aging, which were reversed by exercise. Weight-bearing training promoted protein synthesis in EDL, inhibited protein degradation in EDL, and expression of pyroptotic key proteins in EDL and AT in rats. Conclusion Weight-bearing training improves body composition and alleviates age-related muscle atrophy in rats, and its mechanism may be related to the inhibition of pyroptosis in the EDL and AT and the improvement of muscle protein metabolism.